Immagini del matrimonio ucraino in epoca sovietica tra tradizioni locali ed impronta comunista - Tamara Mykhaylyak (EtnoAntropologia)
This paper describes the major changes that have marked the wedding rituals at the dawn of the Communist regime in Russia. During this transition, the soviet weddings have inevitably drawn from the emerging local traditions reflecting the cultural diversity of the Soviet Union at that time. With specific focus on Ukraine, this paper seeks to show how pictures, thoroughly grouped in a photographic corpus, reveal evidence of that change as well as of those mixed cultural patterns characterising the Western Ukraine families during communism.